Directions for improving customer-oriented policy at small businesses in the field of catering ("Journal "U". Economy. Management. Finance.", 2022)
The article discusses the main directions of development of customer-oriented policy at small businesses in the field of catering, presents the results of a survey of customers of small businesses in the field of catering from the point of view of their satisfaction with the quality of services offered, analyzes the tools used at small businesses in the field of catering to form a customer-oriented policy.
Keywords: catering enterprises; small businesses; questionnaires; customer orientation; the degree of customer satisfaction with the company's services; tools used at small businesses in the service sector for the formation and evaluation of customer-oriented personnel; company website; interactive tablet